Analisis Sentimen dengan Logistic Regression untuk Deteksi Kata pada Livin’ by Mandiri - Ni Made Gita Satviki Nirmala; Ngurah Agus Sanjaya ER (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
Livin by Mandiri is one of the most frequently used mobile banking. To find out the quality of the application, you can carry out sentiment analysis from reviews. The data taken from the Google Play Store was 6334 data from January 2022 to December 2022. The training data and test data used had a ratio of 80:20. This data goes through preprocessing and then TF-IDF weighting is carried out. After that, the analysis used logistic regression which produced 91.5% with C = 0.75. As well as getting negative sentiment results, namely precision 89%, recall 95%, f1-score 92%. Meanwhile, positive sentiment produces 94% precision, 88% recall, 91% f1-score. There is a word detection program that can help search for keywords including positive sentiment or negative sentiment from the Livin by Mandiri application.